High User Satisfaction and Improvement Priorities in Wondr by Bank Negara Indonesia: Kepuasan Pengguna yang Tinggi dan Prioritas Peningkatan di Wondr oleh Bank Negara Indonesia - Dewi Aisarunnisa' Maunah; Rr. Rochmoeljati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of digital technology has transformed the banking industry, leading to the development of mobile banking applications that emphasize user experience and satisfaction. Specific Background: Bank Negara Indonesia (BNI) introduced the Wondr by BNI application as an enhancement to its previous mobile banking service, offering a more integrated financial ecosystem. However, its relatively low user rating compared to its predecessor indicates potential service quality issues. Knowledge Gap: Previous studies have rarely integrated Google’s HEART Metrics and Importance Performance Analysis (IPA) to holistically assess mobile banking user experience. Aims: This study aims to evaluate user satisfaction with Wondr by BNI using HEART Metrics—covering Happiness, Engagement, Adoption, Retention, and Task Success—combined with IPA to identify improvement priorities. Results: The findings reveal that overall satisfaction levels are high, with Happiness, Adoption, and Retention exceeding the 80% usability target, while Engagement and Task Success require improvement. Most attributes fall into the “Maintain Performance” quadrant, though several aspects such as responsiveness and notification reliability remain suboptimal. Novelty: This research uniquely applies a dual-method framework to uncover both experiential and performance-based gaps in mobile banking services. Implications: The results provide strategic insights for optimizing user experience and guiding continuous digital service innovation in Indonesia’s banking sector. Highlights: Combines HEART Metrics and IPA for comprehensive UX evaluation. Identifies key improvement areas in engagement and task success. Provides strategic guidance for enhancing digital banking services. Keywords: HEART Metrics, Importance Performance Analysis, User Satisfaction, Mobile Banking, Wondr by BNI